Electricity Liberalisation in Developing Countries. (April 2017) - Hall, David; Nguyen, Tue Anh
Liberalisation of the electricity sector by unbundling the networks from generation and creating power markets has been promoted to developing countries by the World Bank and others for nearly two decades, in order to stimulate private sector investment. The paper presents cross-country comparisons of progress with liberalisation in the largest developing economies along with investment indicators of generating capacity and access to electricity networks, showing extensive growth in investment regardless of the extent of liberalisation, predominantly by the public sector. The liberalisation model is now losing credibility even in the global north.